2021
DOI: 10.3390/cancers13122965
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase-1-Dependent Methylglyoxal Depletion Sustains PD-L1 Expression in Metastatic Prostate Cancer Cells: A Novel Mechanism in Cancer Immunosurveillance Escape and a Potential Novel Target to Overcome PD-L1 Blockade Resistance

Abstract: Metastatic prostate cancer (mPCa) is a disease for which to date there is not curative therapy. Even the recent and attractive immunotherapeutic approaches targeting PD-L1, an immune checkpoint protein which helps cancer cells to escape from immunosurveillance, have proved ineffective. A better understanding of the molecular mechanisms contributing to keep an immunosuppressive microenvironment associated with tumor progression and refractoriness to PD-L1 inhibitors is urgently needed. In the present study, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Elevation of MG concentration in ATC is coexistent with a decrease in activity of glutathione-glyoxalase 1 (Glo-1). The role of MG and Glo1 seems to be dependent on cancer type, since cancer tissues and cell lines of different molecular background and MG detoxication rate react differently under stress caused by MG [148]. Another in vitro study confirmed that the invasive/migration properties of model ATC cells were associated with accumulation of MG adducts and implementation of aminoguanidine, and that resveratrol decreased the amount of MG adducts.…”
Section: Selected Advanced Glycation End-product Precursors and Rage Ligands As Factors Ofmentioning
confidence: 84%
“…Elevation of MG concentration in ATC is coexistent with a decrease in activity of glutathione-glyoxalase 1 (Glo-1). The role of MG and Glo1 seems to be dependent on cancer type, since cancer tissues and cell lines of different molecular background and MG detoxication rate react differently under stress caused by MG [148]. Another in vitro study confirmed that the invasive/migration properties of model ATC cells were associated with accumulation of MG adducts and implementation of aminoguanidine, and that resveratrol decreased the amount of MG adducts.…”
Section: Selected Advanced Glycation End-product Precursors and Rage Ligands As Factors Ofmentioning
confidence: 84%
“…In the last decade, we have demonstrated that Glo1, by scavenging MG and, consequently by preventing MG-derived MG-H1 formation, plays a pivotal role in PCa progression through both apoptosis [ 20 , 21 ] and EMT [ 22 , 23 ] control. Very recently, we have also found that Glo1/MG-H1 axis contributes to maintaining an immunosuppressive microenvironment by modulating PD-L1 expression [ 24 ]. Here, we added further information to the oncogenic role of the Glo1/MG-H1 pathway in PCa, including it among the mechanisms of PCa cells/OB cross-talk essential to guide bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the Glo1/MG-AGEs axis in PCa progression is today well defined [13]. Glo1 is overexpressed in advanced metastatic PCa, where, through specific MG-derived AGEs, it participates in cancer survival [20,21], PTEN/PI3K/AKT/mTOR signaling-and epithelial-to-mesenchymal transition (EMT)-related metastatic behavior [22,23], in addition, contributes to maintaining an immunosuppressive microenvironment through MG-H1mediated PD-L1 up-regulation [24]. Whether Glo1/MG-H1 axis is also implicated in the mechanisms of PCa cells-driven bone metastases has never been investigated before.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of cancer incidence rate and cell deaths, there have been efforts in developing novel therapeutics for tumor treatment [ 3 , 4 , 5 , 6 ]. Surgery or tumor resection is beneficial in early stages of cancer and when tumor cells diffuse into various tissues in body, it is impossible to eliminate cancer by using surgery [ 7 , 8 ]. Radiotherapy is less invasive compared to surgery, but it has its own problems including side effects and risk of resistance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%